Behavioural activation therapy for adolescents 'at risk' for psychosis?. Issue 2 (23rd June 2014) - Welsh, Patrick; Kitchen, Charlotte E.W.; Ekers, David; Webster, Lisa; Tiffin, Paul A.
Abstract: The following hypothesis explores the possibility of using behavioural activation therapy for adolescents with an at‐risk mental state for psychosis. Support is drawn from psychosis‐related survey and pilot data as well as a robust evidence base for adult depression. However, we acknowledge that extensive feasibility work is required before exploring this hypothesis further.